Assessing Knowledge, Attitudes, and Practices of Medication Disposal: A Study on Rural Communities in Sarojini Nagar, Lucknow - Saurabh Kashyap; Akshata MA; Anubhav Agrawal; Abhishek Singh; Aman Verma; Ish Gupta (Healthline)
Introduction: The increasing global consumption of medications has led to a significant rise in the improper disposal of unused and expired drugs, posing risks to both human health and the environment. Objective: This study aims to evaluate the understanding, beliefs, and behaviours related to the disposal of such medications within the rural community of Sarojini Nagar, Lucknow. Method: A cross-sectional study was conducted in June 2024 with 317 participants from rural Sarojini Nagar, including patients and attendants visiting the General and NCD OPD of PHC Sarojininagar, chosen purposively. Participants aged 18 years and above who provided consent were included, while those with cognitive or communication issues were excluded. Participants were interviewed by Junior Residents and Data was gathered using a structured questionnaire to evaluate demographic characteristics, knowledge, perceptions, attitudes, and practices related to the disposal of unused and expired medications. Results: The study revealed a lack of awareness about proper disposal methods, with 77.3% of participants reporting no prior information on the subject. Only 14.8% were aware of drug take-back policies. A majority (87.9%) recognized the harmful effects of improper disposal, and 93.7% agreed that such practices negatively impact the environment. Despite this, 69.4% of participants reported keeping unused medications at home, and 78.0% disposed of expired medications by throwing them in household trash. Conclusion: The findings highlight a significant gap in knowledge and practices regarding safe drug disposal among rural community of Sarojini Nagar. There is an urgent need for targeted educational programs and the implementation of effective drug take-back systems to mitigate the risks associated with improper disposal. Raising awareness and providing clear guidance on safe disposal methods are crucial steps towards protecting public health and the environment in these communities.